Primera cita de Amaranthus powellii subsp. powellii (Amaranthaceae) para la región del Lazio (Italia Central) con observaciones taxonómicas, morfológicas, corológicas y ecológicas - Iamonico, D. (Universidad de Málaga. Servicio de Publicaciones, 2009)
Amaranthus L. (Amaranthaceae) is a genus consisting of about 70 species, about 40 of which are native to America, while the remaining ones are native to the other continents (Costea et al. 2001). Most of the species recorded in Europe are considered alien species causing social (allergenic plants), economical (crop weeds) and ecological impacts (loss of biodiversity). Moreover, the whole genus is considered critical as for taxonomy and nomenclature, and for the frequent misapplication of names. The Amaranthus hybridus group includes six closely related species (sensu Costea et al. 2001) that are considered the most critical ones both for taxonomy and for morphological variability. Consequently, the identification of the species within this group is very difficult. In this paper, A. powellii S. Watson subsp. powellii is recorded for Lazio region (central Italy) for the first time. The morphology of the species, its distribution, its invasive status, ecological features for Italy and taxonomical notes are also treated. Moreover, a comparison with the related subspecies A. powellii S. Watson subsp. bouchonii (Thell.) Costea & Carretero is provided.
Keywords: Amarantos - Lacio (Italia); Vegetación - Clasificación